DESAIN AIR TRAFFIC SERVICE ROUTE PENERBANGAN SURABAYA MENUJU SINGAPURA DAN MALAYSIA GUNA EFISIENSI PENERBANGAN - Mutiara Ayu Umi Hanifah; Djoko Jatmoko; Lina Rosmayanti; Umi Salamah (Jurnal Manajemen Dirgantara, 2024)
Air traffic service (ATS) routes are essential to optimize flight efficiency, safety, security, and comfort. This study aims to improve safety, operational efficiency, air traffic management, and pilot comfort in the airspace managed by Perum LPPNPI Surabaya Branch by designing a new ATS route. The existing international ATS route from Surabaya to Singapore and Malaysia is limited to one path via RAMPY and SUMDI, which causes inefficiency, traffic conflict, and pilot discomfort. To address these issues, this study conducted an extensive analysis of air traffic data, conflict risk, and operational efficiency. Using a research and development methodology guided by the ICAO 9906 Document Quality Assurance framework, an alternative route named the conventional ATS route was developed based on the user preferred route (UPR) concept. This study used quantitative and qualitative methods, including simulation and data evaluation, to validate the new route. The findings show that the new ATS route significantly improves operational safety and efficiency, reduces traffic conflict, and improves pilot comfort. The new route provides greater flexibility for pilots and supports more effective air traffic management, which is a major improvement over the current route. These improvements are essential to accommodate the ever-increasing demand for air traffic while ensuring safety and comfort. Thus, conventional ATS routes not only address current challenges but also lay the foundation for future improvements in air traffic management and pilot operations, highlighting the importance of continued advancement in aviation infrastructure.